Cervical cancer screening practices among women in Ghana: evidence from wave 2 of the WHO study on global AGEing and adult health - Benedict N. L. Calys-Tagoe; Justice M. K. Aheto; George Mensah; Richard B. Biritwum; Alfred E. Yawson (BMC, 2020)
Abstract Background Cervical cancer is the third most common cancer that affects women worldwide. It has been and remains the leading cause of cancer mortality among women in Ghana. Despite the fact that cervical cancer is preventable through early detection and treatment of precancerous lesions, anecdotal evidence from gynaecological clinics in Ghana indicates that most patients present with a late stage of the disease. This study assesses the cervical cancer screening practices among women in Ghana. Methods Data from the World Health Organization's (WHO) multi-country Study on AGEing and adult health (SAGE) wave 2 conducted between 2014 and 2015 in Ghana was used. We employed binary logistic regression models to analyse data on 2711 women to examine factors associated with having pelvic examination among women aged ≥18 years. Among those who had pelvic examination, we applied binary logistic regression models to analyse factors associated with receiving Pap smear test as a subgroup analysis. Results Of the 2711 women aged 18 years or older surveyed, 225 (8.3%) had ever had a pelvic examination and only 66 (2.4%) of them reported ever having done a Pap smear test. For those who had pelvic examination, only 26.94% had Pap smear test. Ethnic group, marital status, father's educational level and difficulty with self-care were independently associated with undergoing pelvic examination. Only age and healthcare involvement were independently associated with pelvic examination within the past 5 years to the survey. Marital status, satisfaction with healthcare and healthcare involvement were independently associated with Pap smear test. Conclusion Even though cervical cancer is preventable through early detection of precancerous lesions using Pap smear test, the patronage of this screening test is still very low in Ghana. Factors influencing the low patronage in Ghana include the marital status of women, their level of satisfaction with healthcare as well as their level of involvement with healthcare. These may be the consequences of a weak health system and the lack of a national policy on cervical cancer screening.